Complex metal inorganic salt additive for lithium air battery and application of complex metal inorganic salt additive

By introducing SnCl2 into the lithium air battery to form a complex, the problem of blockage of oxygen reduction reaction products caused by superoxide anions is solved, the discharge capacity and cycle life of the lithium air battery are improved, and more efficient electrochemical performance is achieved.

CN119181903APending Publication Date: 2024-12-24JIANGHAN UNIVERSITY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411289837.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Due to the low solubility and high reactivity of superoxide anions, the oxygen reduction reaction products are prone to block the electrodes, affecting their discharge capacity, energy efficiency and cycle life. The existing soluble catalysts cannot effectively improve their discharge capacity.

Method used

SnCl2 is introduced as a metal inorganic salt additive, and by forming a complex with O2-, the solubility of solution phase discharge products is improved, the reactivity of superoxide anions is inhibited, the oxygen reduction reaction path is improved, and the generation of by-products is avoided.

Benefits of technology

The discharge capacity and cycle life of lithium air batteries have been significantly improved, the discharge capacity has been increased by 10 times, the cycle life has been increased by 12 times, and the generation of by-products has been reduced, and the service life of the battery has been extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119181903A_ABST
    Figure CN119181903A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium air batteries, and particularly discloses a complexing type metal inorganic salt additive for a lithium air battery and application of the complexing type metal inorganic salt additive. According to the invention, SnCl2 is introduced into the DMSO electrolyte or diaphragm, and the effect of the DMSO electrolyte or diaphragm is optimal. SnCl2 coated on the diaphragm is gradually released into the DMSO electrolyte, so that Sn < 2 + > is always in saturation concentration; in the charging and discharging process, Sn < 2 + > ions, DMSO and Cl <-> form solvated ions to be complexed with superoxide anions, a Sn < 2 + >-(O < 2->, DMSO and Cl <->)-Li < + > complex is formed, the solubility of O2 in the electrolyte is remarkably improved, and the reactivity of O2 is reduced. The reaction characteristic can realize lithium peroxide liquid phase growth, shows a high-porosity three-dimensional porous particle morphology, and is beneficial to improving the discharge capacity and reversibility. Therefore, excessive SnCl2 is introduced in a diaphragm loading mode, and the discharge capacity and the cycle performance of the lithium air battery can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium-air batteries, and in particular to a lithium-air battery complex-type metal inorganic salt additive and application thereof. Background Art

[0002] As a new type of energy storage and conversion device, lithium-air batteries, which use metallic lithium and oxygen / air as negative and positive active materials respectively, have attracted much attention due to their theoretical energy density comparable to gasoline (3500Wh / kg), clean and environmentally friendly, and low cost. Their theoretical energy density is more than ten times that of lithium-ion batteries, and they have great application prospects.

[0003] However, the current lithium-air battery is still in the laboratory stage, and superoxide anion is widely considered to be the culprit. Its low solubility leads to the solid phase growth of lithium peroxide, the product of oxygen reduction reaction (ORR). The discharge product that tends to grow in the solid phase is easy to block the oxygen diffusion channel of the air electrode and is difficult to decompose during the charging process. These characteristics make lithium-air batteries face several major challenges such as low actual capacity, poor rate performance, low energy efficiency and short cycle life. These aspects greatly limit its practical application development. How to effectively improve the deposition mode of discharge products to improve discharge capacity has always been the focus of previous research. DMSO, as a commonly used electrolyte in lithium-air batteries, can improve the discharge capacity to a certain extent. However, in actual research, DMSO has poor stability and is easily attacked by intermediates such as superoxide and singlet oxygen to produce a variety of byproducts, which seriously affects the cycle life, discharge capacity and rate performance of the battery. Due to the alkaline, nucleophilic and free radical properties of superoxide anion, it will trigger nucleophilic attack, self-oxidation, acid-base reaction and proton-mediated reaction of electrolyte. In order to enhance the solubility of superoxide anions to achieve solution-phase growth of Li2O2, soluble catalysts can be used for regulation. Some progress has been made in ORR catalysts. Unfortunately, most of the current soluble catalyst combinations can enhance their solubility. The increase in solubility increases the presence of superoxide anions, which intensifies side reactions, enhances disproportionation reactions, and releases more aggressive substances, singlet oxygen. Therefore, the discharge capacity of lithium-air batteries cannot be greatly improved, and the advantages of high energy density of lithium-air batteries cannot be achieved.

[0004] Therefore, there is an urgent need for a new type of soluble multifunctional catalyst that can simultaneously increase the solubility of superoxide anions in the electrolyte and reduce their reactivity, so as to improve the actual discharge capacity, energy efficiency and cycle life of lithium-air batteries. Summary of the invention

[0005] In view of the deficiencies in the above-mentioned prior art, the purpose of the present invention is to provide a lithium-air battery complex metal inorganic salt additive and its application. The present invention introduces SnCl2 into the dimethyl sulfoxide (DMSO) electrolyte system and / or the diaphragm. Compared with the two, the latter has better performance, thereby proposing a solution phase growth mechanism of SnCl2-induced discharge products. When SnCl2 is introduced into the lithium-air battery in the form of coating the diaphragm. The dissolved Sn 2+ The ions first undergo a passivation reaction with metallic lithium, and the SnCl2 coated on the diaphragm is gradually released into the DMSO electrolyte system to make Sn 2+ It is always at saturated concentration; thus, in the long-term charge and discharge process, the discharge product is not only formed by conventional electron transfer to form lithium peroxide, but also can change the reaction path of superoxide anions in the DMSO electrolyte system by adjusting its coordination environment in the medium term. 2+ Cations and Cl - The anion enters the coordination shell of the superoxide anion to form Sn 2+ -(O2 - ,DMSO,Cl - )-Li + Complex. Because SnCl2 and O2 - The complex reaction between them will generate more liquid phase discharge intermediates, thereby increasing the solubility of the solution phase discharge products, avoiding the cathode from producing a large number of by-products during the charge and discharge process and thus premature passivation, thereby increasing the discharge capacity. At the same time, it can also inhibit the O2 - The reactivity of the solution phase mechanism is improved to avoid the generation of singlet oxygen, reduce side reactions and mitigate parasitic reactions, including the oxidation of the solvent DMSO to DMSO2, the deposition of byproducts Li2CO3 and LiOH, etc. The discharge product Li2O2 produced by this solution phase mechanism has better charge and discharge reversibility and can improve the cycle life.

[0006] The specific reaction process of adding SnCl2 additive to the DMSO system is shown in the following equation. The discharge process is "Equation 2 → Equation 3 → Equation 4" and the cycle continues, while the charging process is the opposite.

[0007]

[0008] Only when SnCl2 is applied to the lithium-air battery with DMSO electrolyte system in the form of coating the diaphragm can this unique discharge path be continuously formed during the longer charge and discharge process. The discharge products formed can not only avoid the corrosion of superoxide ions on the electrolyte and electrodes, but also improve the stability of the lithium negative electrode, greatly reducing the formation of by-products such as lithium carbonate, dimethyl sulfone, and lithium hydroxide. Therefore, the discharge capacity and cycle performance of the lithium-air battery are significantly improved.

[0009] Electrochemical tests were conducted on lithium-air batteries with SnCl2-loaded membranes, and the results showed that their discharge capacity was 10 times higher than that of lithium-air batteries without SnCl2-loaded membranes, and their cycle life was also increased by 12 times. Electrochemical tests were conducted on lithium symmetric batteries with SnCl2-loaded membranes, and the results showed that their cycle life was increased by 7 times.

[0010] In order to achieve the above object, the present invention adopts the following technical scheme:

[0011] A lithium-air battery comprises a positive electrode, a negative electrode, a separator between the positive and negative electrodes, and an electrolyte. The electrolyte comprises a lithium salt and an organic solvent. The organic solvent is dimethyl sulfoxide (DMSO).

[0012] The lithium-air battery also includes a metal inorganic salt additive, which is SnCl2. The SnCl2 is added by directly introducing it into the electrolyte (I: or the electrolyte also includes SnCl2) or introducing it onto the diaphragm (II: or the diaphragm also includes SnCl2).

[0013] SnCl2 is directly introduced into the electrolyte (I), and the concentration of SnCl2 in the electrolyte is a saturated concentration of 0.02M.

[0014] SnCl2 is introduced onto the diaphragm (II) by mixing SnCl2 with a binder and a conductive agent in an organic solvent to form a slurry, which is then coated on a carrier to form a SnCl2 loaded film. The SnCl2 loaded film and the carrier are an integral whole, called a composite diaphragm. The composite diaphragm is placed between the diaphragm and the negative electrode, and the SnCl2 loaded film is in contact with the diaphragm, and the carrier is in contact with the negative electrode, that is, the SnCl2 loaded film is not in direct contact with the negative electrode. The carrier may be a Celgard2320 diaphragm.

[0015] Specifically, the method of introducing SnCl2 onto the diaphragm includes the following steps:

[0016] SnCl2, a binder and a conductive agent are mixed in nitrogen methyl pyrrolidone NMP at a mass ratio of 7:2:1, with NMP being 4 times the total mass of the solute, and stirred for 5 hours to obtain a mixed slurry; then coated on a carrier, and vacuum dried to obtain a composite diaphragm. The binder can be polyvinylidene fluoride PVDF, the conductive agent can be acetylene black, and the vacuum drying conditions are: drying at 70°C for 24 hours.

[0017] The coating thickness of the SnCl2 loaded film is 100 μm-250 μm, preferably 150 μm-230 μm, more preferably 180-220 μm, and most preferably 200 μm. The coating thickness is preferably not more than 250 μm. The SnCl2 functional additive on the loaded film will be added too much to the electrolyte system in the early stage of charge and discharge, resulting in a supersaturated solution state, causing the electrolyte viscosity to increase, hindering the transmission of lithium ions, affecting the electrochemical reaction activity and thus affecting the overall electrochemical performance.

[0018] Furthermore, the lithium salt is a mixture of one or more of lithium bis(trifluoromethanesulfonyl)imide LiTFSI, lithium bis(fluorosulfonyl)imide LiFSI, and lithium perchlorate LiClO4, preferably lithium bis(trifluoromethanesulfonyl)imide LiTFSI.

[0019] Furthermore, the concentration of lithium salt in the electrolyte is 0.1-10 mol / L, preferably 1 mol / L.

[0020] Furthermore, the negative electrode is a lithium sheet.

[0021] The positive electrode is carbon paper loaded with Ketjen black, and the separator is a glass fiber separator.

[0022] The preparation method of the above-mentioned lithium-air battery comprises the following steps:

[0023] In a glove box, lithium salt and metal inorganic salt additive SnCl2 are added to DMSO, mixed evenly to obtain an electrolyte, and then the positive electrode, separator, negative electrode and electrolyte are assembled into a lithium-air battery; or

[0024] First, the metal inorganic salt additive SnCl2 is mixed with a binder and a conductive agent in an organic solvent to form a slurry, which is then coated on a carrier to form a load film. The load film and the carrier are an integral whole, called a composite diaphragm. Subsequently, in a glove box, lithium salt is added to DMSO and mixed evenly to obtain an electrolyte. Then, the positive electrode, diaphragm, composite diaphragm, negative electrode and electrolyte are assembled into a lithium-air battery. The load film in the composite diaphragm is in contact with the diaphragm, and the carrier is in contact with the negative electrode.

[0025] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0026] The present invention explores the effects of various transition metal ion halide additives on the performance of lithium-air batteries, and finds that the introduction of SnCl2 additives into the electrolyte or onto the diaphragm with dimethyl sulfoxide (DMSO) as the solvent has an improvement effect on the performance of lithium-air batteries. However, only when SnCl2 is applied to the lithium-air battery with DMSO electrolyte in the form of coating the diaphragm can the optimal effect be achieved. This complex metal inorganic salt additive is a new type of additive for lithium-air batteries. The Sn dissolved in the early stage 2+The ions first undergo a passivation reaction with metallic lithium, and then the SnCl2 coated on the diaphragm is gradually released into the DMSO electrolyte system to make Sn 2+ It is always at saturated concentration, so that during long-term charge and discharge, the discharge product is not only formed by conventional electron transfer to form lithium peroxide, but also has strong selectivity. By regulating metal ions, halogen ions and solvents, the catalytic ability of the complex molecule can be improved, and the electrochemical performance of oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) can be improved. During the discharge process, SnCl2 slowly dissolves in the electrolyte, and then the superoxide anion is stabilized by complexing with soluble inorganic SnCl2. SnCl2 and O2 - The complex reaction between them will generate liquid phase discharge intermediates, thereby improving the liquid phase discharge capacity in the donor solvent DMSO, avoiding premature passivation of the cathode and increasing the discharge capacity. At the same time, it can also inhibit O2 - reactivity, avoiding the generation of singlet oxygen, reducing side reactions and improving cycle life.

[0027] In addition, the complex metal inorganic salt additive adopted by the present invention has a low cost and effectively improves the performance of the lithium-air battery. In the electrochemical test of the lithium-air battery, its cycle performance is longer than that of the traditional lithium-air battery without SnCl2 loading membrane, which can reach 340 cycles, and its discharge capacity is 8 times higher than that of the traditional lithium-air battery without SnCl2 loading membrane, which reaches 96013mAh g -1 , the lithium symmetric battery was also electrochemically tested. The lithium symmetric battery with SnCl2 loading film can achieve a cycle life of 1450h. In addition, the carbon cathode and lithium negative electrode after discharge were characterized by scanning electron microscopy (SEM). It can be seen that the battery with SnCl2 loading film makes the discharge product present a fluffy and porous three-dimensional structure, while the battery without SnCl2 loading film has more by-products and presents a dense passivation film. At the same time, the lithium metal anode surface of the lithium symmetric battery with SnCl2 loading film is smoother, which effectively protects it from corrosion by superoxide ions and singlet oxygen. XRD, Raman, and nuclear magnetic resonance (NMR) characterization of the carbon cathode after full discharge all show that the lithium-air battery without SnCl2 loading film has more by-products, such as lithium carbonate, lithium hydroxide, dimethyl sulfone, singlet oxygen, etc., while the lithium-air battery with SnCl2 loading film does not have these by-products, indicating that O2 - The effect on SnCl2 electrolyte is very weak, the reaction activity of O2- is inhibited, the generation of singlet oxygen is avoided, and the stability of the electrolyte is improved. In the lithium-air battery without SnCl2 loading film, O2 - It further reacts with the electrolyte and electrodes to produce by-products such as lithium carbonate, leading to electrode surface passivation and premature termination of discharge. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Impedance spectra of the lithium symmetric batteries assembled in Example 1 and Comparative Example 1 after different cycle times.

[0029] Figure 2 The lithium symmetric battery prepared in Comparative Example 1 and Example 1 was -1 Carbon current density and 2mAh g -1 Cycle time under carbon deposition capacity conditions.

[0030] Figure 3 The lithium-air battery prepared in Comparative Example 1 and Example 1 was -1 , 500mAg -1 , 1000mAg -1 Rate performance and discharge capacity measured under current density.

[0031] Figure 4 The voltage polarization diagram corresponding to the first 20 cycles of the lithium-air batteries prepared in Comparative Example 1 and Example 1.

[0032] Figure 5 This is the positive electrode Raman spectrum of the lithium-air battery assembled in Comparative Example 1 and Example 1 after complete discharge.

[0033] Figure 6 XRD patterns of the positive electrodes of the lithium-air batteries assembled in Comparative Example 1 and Example 1 after full discharge.

[0034] Figure 7 This is a SEM image of the positive electrode of the lithium-air battery prepared in Comparative Example 1 after full discharge.

[0035] Figure 8 This is a SEM image of the positive electrode of the lithium-air battery prepared in Example 1 after full discharge.

[0036] Fig. 9 This is the SEM image of the lithium negative electrode of the lithium symmetric battery prepared in Comparative Example 1 after cycling for 100 hours.

[0037] Fig.10 This is the SEM image of the lithium negative electrode of the lithium symmetric battery prepared in Example 1 after cycling for 100 hours.

[0038] Fig.11 The nuclear magnetic resonance (NMR) H spectra of the lithium-air batteries assembled in Comparative Example 1 and Example 1 are shown.

[0039] Fig.12 The nuclear magnetic resonance (NMR) C spectra of the lithium-air batteries assembled in Comparative Example 1 and Example 1 are shown.

[0040] Fig.13The cycle performance of the lithium-air batteries corresponding to Comparative Example 1, Example 1, Comparative Example 9 and Comparative Example 10.

[0041] Fig.14 Mechanism diagram of the DMSO electrolyte system without SnCl2 loaded membrane and with SnCl2 loaded membrane.

[0042] For simplicity in the accompanying drawings, the lithium-air battery or lithium symmetrical battery assembled / prepared in Comparative Example 1 is denoted as Blank; the lithium-air battery or lithium symmetrical battery assembled / prepared in Example 1 is denoted as SnCl2. DETAILED DESCRIPTION

[0043] The present invention will be described in detail below in conjunction with the embodiments and drawings, and the advantages and various effects of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific embodiments are used to illustrate the present invention, rather than to limit the present invention.

[0044] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.

[0045] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0046] Embodiment 1:

[0047] 1. Preparation of coating slurry

[0048] (1) 700 mg SnCl2, 200 mg polyvinylidene fluoride PVDF and 100 mg acetylene black are taken in a ratio of 7:2:1, respectively, and mixed in 4 g NMP nitrogen methyl pyrrolidone to obtain a mixed solution, wherein the NMP is 4 times the total mass of the solute (the prepared mixed solution can evenly disperse the solute);

[0049] (2) stirring the obtained mixed solution at 40° C. for 5 h to obtain a mixed slurry (stirring for 5 h can make the solute evenly dispersed and have a moderate viscosity; if the stirring time is too short, the slurry will be too viscous and the coating of the active material will be uneven; if the stirring time is too long, the solvent will evaporate too quickly, causing the slurry to dry up and thus affecting the coating);

[0050] 2. Preparation of diaphragm containing SnCl2 additive slurry

[0051] The obtained mixed slurry was evenly coated on the Celgard2320 diaphragm with a small coating machine. The thickness of the coating was controlled at 200μm and vacuum dried at 70℃ for 24h to obtain a composite diaphragm (vacuum drying at 70℃ can completely evaporate the solvent on the surface; both too low and too high temperatures will affect the performance of the composite diaphragm. Too low temperature will cause the surface solvent to not completely evaporate, and too high temperature will cause the composite diaphragm to curl). Considering the solubility of the SnCl2 additive, if the metal chloride of the 200μm coating can be completely dissolved in the electrolyte, the SnCl2 concentration is about 0.05mol / L.

[0052] 3. Battery assembly and testing

[0053] (1) Assembly of lithium-air battery: the composite diaphragm prepared in step 2 is placed between the glass fiber diaphragm Whatman GF / D and the negative electrode lithium sheet, with the side of the composite diaphragm with SnCl2 additive facing the glass fiber diaphragm and the other side facing the lithium negative electrode, wherein the diameter of the lithium sheet is 16 mm and the thickness is 0.45 mm; meanwhile, the positive electrode substrate is made of carbon paper with a diameter of 12 mm and a carbon paper loading of 0.11 mg / cm 2 Ketjen black; the electrolyte is 1 mol / L lithium bis(trifluoromethanesulfonyl)imide (LiTFSI is lithium salt, the solvent is dimethyl sulfoxide (DMSO), and they are assembled into a lithium-air battery.

[0054] (2) Lithium-air battery assembly and testing were carried out under the following conditions: ① The water content in the glove box was limited to less than 0.01ppm. ② The gas atmosphere was 80% nitrogen and 20% oxygen. ③ The battery case was CR-2032 type. ④ The discharge capacity and cycle life were tested using the Xinwei system. ⑤ The discharge capacity of the lithium-air battery was 100mAg -1 、500mAg -1 , 1000mAg -1 The current density is obtained by discharge test under the condition of 2V cut-off voltage; the cycle life of lithium-air battery is 500mAg -1 Current density, cut-off 1000mAhg -1 The test results are obtained under the conditions of charge and discharge specific capacity.

[0055] (3) Assembly of a lithium symmetrical battery. The composite diaphragm prepared in step 2 is placed between the glass fiber diaphragm Whatman GF / D and the negative electrode lithium sheet. The side of the composite diaphragm with the SnCl2 additive faces the glass fiber diaphragm, and the other side faces the lithium negative electrode. The diameter of the lithium sheet is 16 mm and the thickness is 0.45 mm. At the same time, the positive electrode also uses a lithium sheet with the same specifications and dimensions as the lithium metal negative electrode. The electrolyte is 1 mol / L lithium bis(trifluoromethanesulfonic acid) imide (LiTFSI is the lithium salt and the solvent is dimethyl sulfoxide (DMSO). They are assembled into a lithium symmetrical battery.

[0056] (4) The lithium symmetric battery assembly and testing were carried out under the following conditions: ① The water content in the glove box was limited to less than 0.01ppm. ② The gas atmosphere was high-purity argon with a purity of >99.99%. ③ The battery case was CR-2032 type. ④ The cycle life of the lithium symmetric battery was tested using the Xinwei system. ⑤ The cycle life of the lithium symmetric battery was tested at 1mAg -1 Carbon current density and 2mAh g -1 The results are obtained by testing under carbon deposition capacity conditions.

[0057] The lithium-air battery in this embodiment is tested at 100 mAg -1 The discharge capacity measured under the current density test conditions is 96013mAh g -1 , at a current density of 500mAg -1 , cut-off capacity is 1000mAhg -1 The number of cycles under the condition of 1000 cycles reaches 340 cycles. The lithium symmetric battery of this embodiment can achieve a stable cycle time of 1450h. For specific performance description, please refer to the legend.

[0058] Embodiment 2:

[0059] 1. Preparation of electrolyte containing SnCl2 additive

[0060] (1) LiTFSI is used as lithium salt, DMSO is used as solvent, and a metal inorganic salt additive SnCl2 is added and mixed evenly; the mixed solution is stirred until the solute is completely dissolved to obtain a mixed electrolyte, wherein the concentration of the stannous chloride additive in the mixed electrolyte is a saturated concentration of 0.02 mol / L, and the concentration of LiTFSI is 1 mol / L.

[0061] 2. Battery assembly and testing.

[0062] (1) Assembly of lithium-air batteries: In a glove box, lithium-air batteries were assembled, wherein the negative electrode was a lithium negative electrode, the diameter of the lithium sheet was 16 mm, and the thickness was 0.45 mm; meanwhile, the positive electrode substrate was a carbon paper with a diameter of 12 mm, wherein the carbon paper loading was 0.1 mg / cm 2 Ketjen black; the electrolyte is the electrolyte prepared in step 1, and the diaphragm model is glass fiber Whatman GF / D, and they are assembled into a lithium-air battery.

[0063] (2) Lithium-air battery assembly and testing were carried out under the following conditions: ① The water content in the glove box was limited to less than 0.01ppm. ② The gas atmosphere was 80% nitrogen and 20% oxygen. ③ The battery case was CR-2032 type. ④ The discharge capacity and cycle life were tested using the Xinwei system. ⑤ The discharge capacity of the lithium-air battery was 100mAg -1 、500mAg -1, 1000mAg -1 Current density, obtained by discharge test under 2V cut-off voltage condition; the cycle life of lithium-air battery is 500mAg -1 Current density, cut-off 1000mAhg -1 The test results are obtained under the conditions of charge and discharge specific capacity. Please refer to the legend for specific performance description.

[0064] The lithium-air battery in this embodiment is 100mAg -1 The discharge capacity measured under the current density test conditions is 76002mAh g -1 , at a current density of 500mAg -1 , cut-off capacity is 1000mAhg -1 Under the condition of , the number of cycles reaches 235.

[0065] Embodiment 3:

[0066] In Example 3, lithium bis(fluorosulfonyl)imide LiFSI is used as the lithium salt, the concentration of LiFSI is 1 mol / L, and the remaining steps are the same as in Example 1.

[0067] Example 3 Lithium-air battery at 100mAg -1 The discharge capacity measured under the current density test conditions is 86301mAh g -1 , the number of cycles reaches 258.

[0068] It should be noted that the positive and negative electrode materials of this embodiment are the same as those of embodiment 1, and the thickness / diameter / load of both should be the same. The lithium-air battery assembly and test conditions are also the same as those of embodiment 1.

[0069] Embodiment 4:

[0070] In Example 4, lithium bis(fluorosulfonyl)imide LiFSI is used as the lithium salt, the concentration of LiFSI is 1 mol / L, and the remaining steps are the same as in Example 2.

[0071] Example 4 Lithium-air battery at 100mAg -1 The discharge capacity measured under the current density test conditions is 72628 mAh g -1 , at a current density of 500mAg -1 , cut-off capacity is 1000mAhg -1 Under the condition of , the number of cycles reaches 192.

[0072] It should be noted that the positive and negative electrode materials of this embodiment are the same as those of embodiment 2, and the thickness / diameter / load of the two should be the same. The lithium-air battery assembly and test conditions are also the same as those of embodiment 2.

[0073] Embodiment 5:

[0074] In Example 4, lithium perchlorate LiClO4 is used as the lithium salt, the concentration of LiClO4 is 1 mol / L, and the remaining steps are the same as those in Example 1.

[0075] Example 4 Lithium-air battery at 100mAg -1 The discharge capacity measured under the current density test conditions is 82635mAh g -1 , at a current density of 500mAg -1 , cut-off capacity is 1000mAhg -1 Under the condition of , the number of cycles reaches 267.

[0076] It should be noted that the positive and negative electrode materials of this embodiment are the same as those of embodiment 1, and the thickness / diameter / load of both should be the same. The lithium-air battery assembly and test conditions are also the same as those of embodiment 1.

[0077] Embodiment 6:

[0078] In Example 6, lithium perchlorate LiClO4 is used as the lithium salt, the concentration of LiClO4 is 1 mol / L, and the remaining steps are the same as those in Example 2.

[0079] Example 6 Lithium-air battery at 100mAg -1 The discharge capacity obtained under the current density test conditions is 71815 mAh g -1 , at a current density of 500mAg -1 , cut-off capacity is 1000mAhg -1 Under the condition of , the number of cycles reaches 189.

[0080] It should be noted that the positive and negative electrode materials of this embodiment are the same as those of embodiment 2, and the thickness / diameter / load of the two should be the same. The lithium-air battery assembly and test conditions are also the same as those of embodiment 2.

[0081] Embodiment 7:

[0082] Preparation of diaphragms with different thicknesses containing SnCl2 additive slurry

[0083] The obtained mixed slurry was evenly coated on the Celgard2320 diaphragm with a small coating machine. The coating thickness was controlled at 50 μm and vacuum dried at 70°C for 24 h to obtain a composite diaphragm. Considering the solubility of the SnCl2 additive, the metal chloride of the 50 μm coating could be completely dissolved in the electrolyte, and the SnCl2 concentration was about 0.0125 mol / L.

[0084] Example 7 Lithium-air battery at 100mAg -1The discharge capacity measured under the current density test conditions is 30807mAh g -1 , at a current density of 500mAg -1 , cut-off capacity is 1000mAhg -1 Under the condition of , the number of cycles reaches 143.

[0085] It should be noted that the remaining steps of this embodiment are the same as those of embodiment 1, and the positive and negative electrode materials of this embodiment are the same as those of embodiment 1, and the thickness / diameter / load of both should be the same. The lithium-air battery assembly and test conditions are also the same as those of embodiment 1.

[0086] Embodiment 8:

[0087] Preparation of diaphragms with different thicknesses containing SnCl2 additive slurry

[0088] The obtained mixed slurry was evenly coated on the Celgard2320 diaphragm with a small coating machine. The coating thickness was controlled at 100 μm and vacuum dried at 70°C for 24 h to obtain a composite diaphragm. Considering the solubility of the SnCl2 additive, if the metal chloride of 100 μm coating can be completely dissolved in the electrolyte, the SnCl2 concentration is about 0.025 mol / L.

[0089] Example 8 Lithium-air battery at 100mAg -1 The discharge capacity measured under the current density test conditions is 77807 mAh g -1 , at a current density of 500mAg -1 , cut-off capacity is 1000mAhg -1 Under the condition of , the number of cycles reaches 266.

[0090] It should be noted that the remaining steps of this embodiment are the same as those of embodiment 1, and the positive and negative electrode materials of this embodiment are the same as those of embodiment 1, and the thickness / diameter / load of both should be the same. The lithium-air battery assembly and test conditions are also the same as those of embodiment 1.

[0091] Embodiment 9:

[0092] Preparation of diaphragms with different thicknesses containing SnCl2 additive slurry

[0093] The obtained mixed slurry was evenly coated on the Celgard2320 diaphragm with a small coating machine. The coating thickness was controlled at 150μm and vacuum dried at 70°C for 24h to obtain a composite diaphragm. Considering the solubility of the SnCl2 additive, if the metal chloride of the 150μm coating can be completely dissolved in the electrolyte, the SnCl2 concentration is about 0.0375mol / L.

[0094] Example 9 Lithium-air battery at 100mAg-1 The discharge capacity measured under the current density test conditions is 82510 mAh g -1 , at a current density of 500mAg -1 , cut-off capacity is 1000mAhg -1 Under the condition of , the number of cycles reaches 287.

[0095] It should be noted that the remaining steps of this embodiment are the same as those of embodiment 1, and the positive and negative electrode materials of this embodiment are the same as those of embodiment 1, and the thickness / diameter / load of both should be the same. The lithium-air battery assembly and test conditions are also the same as those of embodiment 1.

[0096] Embodiment 10:

[0097] Preparation of diaphragms with different thicknesses containing SnCl2 additive slurry

[0098] The obtained mixed slurry was evenly coated on the Celgard2320 diaphragm with a small coating machine. The coating thickness was controlled at 250μm and vacuum dried at 70°C for 24h to obtain a composite diaphragm. Considering the solubility of the SnCl2 additive, if the metal chloride of the 250μm coating can be completely dissolved in the electrolyte, the SnCl2 concentration is about 0.0625mol / L.

[0099] Example 10 Lithium-air battery at 100mAg -1 The discharge capacity tested under the current density test conditions is 80000mAh g -1 , at a current density of 500mAg -1 , cut-off capacity is 1000mAhg -1 Under the condition of , the number of cycles reaches 274.

[0100] It should be noted that the remaining steps of this embodiment are the same as those of embodiment 1, and the positive and negative electrode materials of this embodiment are the same as those of embodiment 1, and the thickness / diameter / load of both should be the same. The lithium-air battery assembly and test conditions are also the same as those of embodiment 1.

[0101] Embodiment 11:

[0102] Preparation of diaphragms with different thicknesses containing SnCl2 additive slurry

[0103] The obtained mixed slurry was evenly coated on the Celgard2320 diaphragm with a small coating machine. The coating thickness was controlled at 300μm and vacuum dried at 70℃ for 24h to obtain a composite diaphragm. Considering the solubility of the SnCl2 additive, if the metal chloride of 300μm coating can be completely dissolved in the electrolyte, the SnCl2 concentration is about 0.075mol / L.

[0104] Example 11 Lithium-air battery at 100mAg -1 The discharge capacity measured under the current density test conditions is 69581mAh g -1 , at a current density of 500mAg -1 , cut-off capacity is 1000mAhg -1 Under the condition of , the number of cycles reaches 198.

[0105] It should be noted that the remaining steps of this embodiment are the same as those of embodiment 1, and the positive and negative electrode materials of this embodiment are the same as those of embodiment 1, and the thickness / diameter / load of both should be the same. The lithium-air battery assembly and test conditions are also the same as those of embodiment 1.

[0106] Comparative Example 1:

[0107] 1. Prepare the lithium-air electrolyte of Comparative Example 1

[0108] (1) LiTFSI is used as the lithium salt and DMSO is used as the solvent to prepare the lithium-air electrolyte of Comparative Example 1, wherein the concentration of LiTFSI in the electrolyte is 1 mol / L.

[0109] 2. Battery assembly and testing.

[0110] (1) Assembly of lithium-air batteries: In a glove box, lithium-air batteries were assembled, wherein the negative electrode was a lithium negative electrode, the diameter of the lithium sheet was 16 mm, and the thickness was 0.45 mm; meanwhile, the positive electrode substrate used a carbon paper with a diameter of 12 mm as the positive electrode, wherein the carbon paper loading was 0.11 mg / cm 2 Ketjen black; the electrolyte is the lithium-air electrolyte prepared in step 1, and the diaphragm model is glass fiber Whatman GF / D, and they are assembled into a lithium-air battery.

[0111] (2) Lithium-air battery assembly and testing were carried out under the following conditions: ① The water content in the glove box was limited to less than 0.01ppm; ② The gas atmosphere was 80% nitrogen and 20% oxygen; ③ The battery case was CR-2032 type. ④ The discharge capacity and cycle life were tested using the Xinwei system. ⑤ The discharge capacity of the lithium-air battery was 100mAg -1 、500mAg -1 , 1000mAg -1 Current density, obtained by discharge test under 2V cut-off voltage condition; the cycle life of lithium-air battery is 500mAg -1 Current density, cut-off 1000mAhg -1 The test results are obtained under the conditions of charge and discharge specific capacity.

[0112] (3) Assembly of a lithium symmetrical battery. The negative electrode is a lithium sheet with a diameter of 16 mm and a thickness of 0.45 mm. The positive electrode is also a lithium sheet with the same specifications and dimensions as the lithium metal negative electrode. The positive electrode and the lithium sheet are separated by glass fiber. The electrolyte is 1 mol / L lithium bis(trifluoromethanesulfonic acid)imide (LiTFSI is the lithium salt and the solvent is dimethyl sulfoxide (DMSO). They are assembled into a lithium symmetrical battery.

[0113] (4) The lithium symmetric battery assembly and testing were carried out under the following conditions: ① The water content in the glove box was limited to less than 0.1ppm. ② The gas atmosphere was high-purity argon with a purity of >99.99%. ③ The battery case was CR-2032 type. ④ The cycle life of the lithium symmetric battery was tested using the Xinwei system. ⑤ The cycle time of the lithium symmetric battery was 1mAg -1 Carbon current density and 2mAhg -1 The results are obtained by testing under carbon deposition capacity conditions.

[0114] The lithium-air battery measured in Comparative Example 1 is -1 The discharge capacity measured under the current density test conditions is 13210 mAh g -1 , at a current density of 500mAg -1 , cut-off capacity is 1000mAhg -1 Under the condition of , the number of cycles reaches 20; the lithium symmetric battery in this comparative example can only reach a stable cycle time of 250h. For specific performance description, please refer to the legend.

[0115] The battery assembled in this comparative example was attacked by superoxide ions, which converted the DMSO into DMSO2. Singlet oxygen was also produced during the reaction, which promoted the production of lithium carbonate as a byproduct. The mechanism can be seen in the attached Fig.14 .

[0116] Comparative Example 2A:

[0117] In Comparative Example 2A, the solvent DMSO was replaced by tetraethylene glycol dimethyl ether TEGDME, and the remaining steps were the same as those in Example 1.

[0118] In comparative example 2A, the lithium-air battery is at 100 mAg -1 The discharge capacity measured under the current density test conditions is 33897 mAh g -1 , at a current density of 500mAg -1 , cut-off capacity is 1000mAhg -1 Under the condition of , the number of cycles reaches 113.

[0119] It should be noted that the positive and negative electrode materials of this comparative example are the same as those of Example 1, and the thickness / diameter / load of both should be uniform. The lithium-air battery assembly and test conditions are also the same as those of Example 1.

[0120] Comparative Example 2B:

[0121] In Comparative Example 2B, the solvent DMSO was replaced by tetraethylene glycol dimethyl ether TEGDME, and the remaining steps were the same as in Example 2.

[0122] In Comparative Example 2B, the lithium-air battery is -1 The discharge capacity measured under the current density test conditions is 30613 mAh g -1 , at a current density of 500mAg -1 , cut-off capacity is 1000mAhg -1 Under the condition of , the number of cycles reaches 100.

[0123] It should be noted that the positive and negative electrode materials of this comparative example are the same as those of Example 2, and the thickness / diameter / load of both should be uniform. The lithium-air battery assembly and test conditions are also the same as those of Example 2.

[0124] Comparative Example 3A:

[0125] In Comparative Example 3A, the solvent DMSO was replaced by propylene carbonate PC, and the remaining steps were the same as in Example 1.

[0126] In comparative example 3A, the lithium-air battery is -1 The discharge capacity obtained under the current density test conditions is 9897 mAh g -1 , at a current density of 500mAg -1 , cut-off capacity is 1000mAhg -1 Under the condition of , the number of cycles reaches 43.

[0127] It should be noted that the positive and negative electrode materials of this comparative example are the same as those of Example 1, and the thickness / diameter / load of both should be uniform. The lithium-air battery assembly and test conditions are also the same as those of Example 1.

[0128] Comparative Example 3B:

[0129] In Comparative Example 3B, the solvent DMSO was replaced by propylene carbonate PC, and the remaining steps were the same as those in Example 2.

[0130] In Comparative Example 3B, the lithium-air battery is -1 The discharge capacity measured under the current density test conditions is 7694 mAh g -1 , at a current density of 500mAg-1 , cut-off capacity is 1000mAhg -1 Under the condition of , the number of cycles reaches 38.

[0131] It should be noted that the positive and negative electrode materials of this comparative example are the same as those of Example 2, and the thickness / diameter / load of both should be uniform. The lithium-air battery assembly and test conditions are also the same as those of Example 2.

[0132] Comparative Example 4A:

[0133] In Comparative Example 4A, the solvent DMSO was replaced by a mixture of propylene carbonate PC and DMSO in a volume ratio of 1:1, and the remaining steps were the same as in Example 1.

[0134] In comparative example 4A, the lithium-air battery is -1 The discharge capacity measured under the current density test conditions is 25780mAh g -1 , at a current density of 500mAg -1 , cut-off capacity is 1000mAhg -1 Under the condition of , the number of cycles reaches 68.

[0135] It should be noted that the positive and negative electrode materials of this comparative example are the same as those of Example 1, and the thickness / diameter / load of both should be uniform. The lithium-air battery assembly and test conditions are also the same as those of Example 1.

[0136] Comparative Example 4B:

[0137] In Comparative Example 4B, the solvent DMSO was replaced by a mixture of propylene carbonate PC and DMSO in a volume ratio of 1:1, and the remaining steps were the same as those in Example 2.

[0138] In Comparative Example 4B, the lithium-air battery is -1 The discharge capacity measured under the current density test conditions is 21697 mAh g -1 , at a current density of 500mAg -1 , cut-off capacity is 1000mAhg -1 Under the condition of , the number of cycles reaches 64.

[0139] It should be noted that the positive and negative electrode materials of this comparative example are the same as those of Example 2, and the thickness / diameter / load of both should be uniform. The lithium-air battery assembly and test conditions are also the same as those of Example 2.

[0140] Comparative Example 5:

[0141] 1. Prepare electrolyte of comparative example 5

[0142] LiTFSI is used as the lithium salt, DMSO is used as the solvent, and SnBr2 is added as an additive to form a mixed lithium-air electrolyte. The concentration of LiTFSI in the electrolyte is 1 mol / L, and the concentration of SnBr2 is 0.02 mol / L.

[0143] 2. Battery assembly and testing.

[0144] (1) Assembly of lithium-air batteries: In a glove box, lithium-air batteries were assembled, wherein the negative electrode was a lithium negative electrode, the diameter of the lithium sheet was 16 mm, and the thickness was 0.45 mm; meanwhile, the positive electrode substrate used a carbon paper with a diameter of 12 mm as the positive electrode, wherein the carbon paper loading was 0.11 mg / cm 2 Ketjen black; the electrolyte is the electrolyte prepared in step 1, and the diaphragm model is glass fiber Whatman GF / D, and they are assembled into a lithium-air battery.

[0145] (2) Lithium-air battery assembly and testing were carried out under the following conditions: ① The water content in the glove box was limited to less than 0.01ppm. ② The gas atmosphere was 80% nitrogen and 20% oxygen. ③ The battery case was CR-2032 type. ④ The discharge capacity and cycle life were tested using the Xinwei system. ⑤ The discharge capacity of the lithium-air battery was 100mAg -1 、500mAg -1 , 1000mAg -1 Current density, obtained by discharge test under 2V cut-off voltage condition; the cycle life of lithium-air battery is 500mAg -1 Current density, cut-off 1000mAhg -1 The test results are obtained under the conditions of charge and discharge specific capacity.

[0146] The lithium-air battery measured in Comparative Example 5 is -1 The discharge capacity measured under the current density test conditions is 19873 mAh g -1 , the number of cycles reaches 84.

[0147] It should be noted that the positive and negative electrode materials of this comparative example are the same as those of Example 2, and the thickness / diameter / load of both should be uniform. The lithium-air battery assembly and test conditions are also the same as those of Example 2.

[0148] Comparative Example 6:

[0149] The SnCl2 in Example 1 is replaced by SnBr2, and the remaining steps are the same as in Example 1.

[0150] The lithium-air battery measured in Comparative Example 6 is -1 The discharge capacity obtained under the current density test conditions is 22289 mAh g -1 , the number of cycles reaches 112.

[0151] Comparative Example 7:

[0152] 1. Prepare electrolyte of comparative example 7

[0153] LiTFSI is used as the lithium salt, DMSO is used as the solvent, and SnI2 additive is added to form a mixed lithium-air electrolyte. The concentration of LiTFSI in the electrolyte is 1 mol / L, and the concentration of SnI2 is 0.02 mol / L.

[0154] The application performance test steps of this comparative example are the same as those of comparative example 5.

[0155] The lithium-air battery measured in Comparative Example 7 is -1 The discharge capacity measured under the current density test conditions is 20846 mAh g -1 , the number of cycles reaches 94.

[0156] It should be noted that the positive and negative electrode materials of this comparative example are the same as those of Example 2, and the thickness / diameter / load of both should be uniform. The lithium-air battery assembly and test conditions are also the same as those of Example 2.

[0157] Comparative Example 8:

[0158] The SnCl2 in Example 1 is replaced by SnI2, and the remaining steps are the same as in Example 1.

[0159] The lithium-air battery measured in Comparative Example 8 is -1 The discharge capacity measured under the current density test conditions is 23518 mAh g -1 , the number of cycles reached 119.

[0160] Comparative Example 9:

[0161] 1. Prepare electrolyte of comparative example 9

[0162] LiTFSI is used as lithium salt, DMSO is used as solvent, and ZnCl2 additive is added to form a mixed lithium-air electrolyte. The concentration of LiTFSI in the electrolyte is 1 mol / L, and the concentration of ZnCl2 is 0.02 mol / L.

[0163] The application performance test steps of this comparative example are the same as those of comparative example 5.

[0164] The lithium-air battery measured in Comparative Example 9 is -1 The discharge capacity obtained under the current density test conditions is 15400mAh g -1 , the number of cycles reaches 55.

[0165] It should be noted that the positive and negative electrode materials of this comparative example are the same as those of Example 2, and the thickness / diameter / load of both should be uniform. The lithium-air battery assembly and test conditions are also the same as those of Example 2.

[0166] Comparative Example 10:

[0167] 1. Preparation of ZnCl2 additive slurry diaphragm

[0168] The SnCl2 in Example 1 is replaced by ZnCl2, and the remaining steps are the same as in Example 1.

[0169] The lithium-air battery measured in Comparative Example 10 is -1 The discharge capacity measured under the current density test conditions is 18868 mAh g -1 , the number of cycles reaches 68.

[0170] Attached Figure 1-Figure 13 Related instructions:

[0171] Figure 1 The impedance spectra of the lithium symmetric batteries prepared in Comparative Example 1 and Example 1 after different cycle times are shown. After 100 hours, the impedance of the battery assembled in Comparative Example 1 increased significantly from 115Ω to 1250Ω, while the impedance of the battery assembled in Example 1 with the SnCl2 loading membrane only increased slightly from 75Ω to 750Ω, which indicates that the free Cl in the electrolyte of the battery with the SnCl2 loading membrane is - Not only does it increase ionic conductivity, but it also 2+ The alloy phase produced by the interaction with the lithium metal surface protects the negative electrode and inhibits the occurrence of side reactions, thereby achieving good electrochemical impedance performance.

[0172] Figure 2 The lithium symmetric battery prepared in Comparative Example 1 and Example 1 is 1 mAg -1 Carbon current density and 2mAhg -1 The cycle time under the condition of carbon deposition capacity shows that the lithium symmetric battery assembled in comparative example 1 died after working for 250 hours. In contrast, the symmetric lithium battery assembled in example 1 can be stably cycled for 1450 hours, and the polarization voltage is always less than 0.5 mV, which is 5.8 times that of the comparative battery.

[0173] Figure 3 The lithium-air battery prepared in Comparative Example 1 and Example 1 was -1 , 500mAg -1 , 1000mAg -1The rate performance and discharge capacity measured under current density show that the discharge capacity of the lithium-air battery with the addition of SnCl2 load membrane is significantly improved, which is 10 times that of the battery without the addition of SnCl2 load membrane, and the rate performance is also greatly improved.

[0174] Figure 4 The voltage polarization diagram of the lithium-air battery prepared in Comparative Example 1 and Example 1 corresponding to the first 20 cycles, wherein the charge and discharge current density is 500 mAg -1 , cut-off charge and discharge specific capacity 1000mAhg -1 From this figure, it can be found that the lithium-air battery prepared in Example 1 has smaller polarization and more stable cycle, so it can maintain a long cycle life.

[0175] Figure 5 The positive electrode Raman spectra of the lithium-air batteries assembled in Comparative Example 1 and Example 1 after complete discharge, the discharge product Li2O2 and the byproduct Li2CO3 can be clearly observed in Comparative Example 1, and the Raman peak of the battery assembled in Example 1 only observes the discharge product Li2O2, and no Li2CO3 and other byproducts are detected. This shows that the addition of SnCl2 additive effectively inhibits the attack of superoxide ions and singlet oxygen on the system, and stabilizes the entire lithium-air battery system.

[0176] Figure 6 The positive electrode XRD patterns of the lithium-air batteries assembled in Comparative Example 1 and Example 1 after complete discharge, the discharge product Li2O2 and the byproduct Li2CO3 were clearly observed in the battery assembled in Comparative Example 1. When the battery of Example 1 was tested under the same conditions, only Li2O2 was observed by XRD, and no byproduct Li2CO3 was observed, which also shows that adding SnCl2 to the lithium-air battery with DMSO as the electrolyte organic solvent can significantly inhibit the side reaction and improve the overall performance.

[0177] Figure 7 This is the SEM image of the positive electrode of the lithium-air battery prepared in Comparative Example 1 after full discharge. In addition to the discharge product lithium peroxide, there are also many by-products that block the positive electrode. The deposition on the positive electrode surface is very dense, forming a dense passivation film, which hinders the subsequent Li + The electrochemical reaction channel with oxygen leads to lower discharge specific capacity and shorter cycle life.

[0178] Figure 8 This is the SEM image of the positive electrode of the lithium-air battery prepared in Example 1 after full discharge. It can be seen that the morphology of the discharged positive electrode of the lithium-air battery with the addition of the SnCl2 load film is completely different from that of Comparative Example 1. There are no obvious deposited by-products, and all are three-dimensionally deposited lithium peroxide, which will not clog the positive electrode and has a higher discharge capacity.

[0179] Fig. 9This is the SEM image of the lithium negative electrode of the lithium symmetric battery prepared in Comparative Example 1 after 100 hours of cycling. It can be seen that there are many blocky by-products on the surface of the lithium sheet. This is due to the corrosion of the lithium negative electrode caused by redox intermediates and electrolyte by-products, which will lead to a decrease in the cycle life of the lithium-air battery.

[0180] Fig.10 The SEM image of the lithium negative electrode of the lithium symmetric battery prepared in Example 1 after 100 hours of cycling, and Fig. 9 There is an obvious difference. There is no obvious granular by-product generated on the surface of the lithium sheet, and the surface of the lithium sheet is relatively smooth, which proves that the SnCl2 loading film has a protective effect on the lithium negative electrode. Therefore, the discharge capacity and cycle life of the lithium-air battery with the addition of the SnCl2 loading film are greatly improved.

[0181] Fig.11 The nuclear magnetic resonance (NMR) H spectra of the lithium-air batteries prepared in Example 1 and Comparative Example 1 are shown in FIG. Fig.12 The NMR C spectra of the lithium-air batteries prepared in Example 1 and Comparative Example 1 are shown. DMSO2 was observed in the lithium-air battery in Comparative Example 1 after discharge, while DMSO2 was not observed in the lithium-air battery in Example 1 after discharge, indicating that O2 - The effect on SnCl2 electrolyte is very weak, O2 - The reactivity of the electrolyte is suppressed and the stability of the electrolyte is improved.

[0182] Fig.13 The cycle performance of the lithium-air batteries corresponding to Comparative Example 1, Example 1, Comparative Example 9 and Comparative Example 10 shows that the electrolyte with the SnCl2 additive is more stable as a whole and the overall performance of the battery is better.

[0183] It can be seen from the above embodiments, comparative examples and accompanying drawings that:

[0184] In an electrolyte system using DMSO as a solvent, the introduction of SnCl2 functional additives can enable the assembled lithium-air battery to have a higher discharge specific capacity and cycle life, far exceeding the effect of introducing SnBr2, SnI2, and ZnCl2 additives (Comparative Examples 5-7, Comparative Examples 8-10). The present invention stabilizes the DMSO electrolyte system by introducing the SnCl2 functional additive, and greatly improves the performance of the DMSO electrolyte.

[0185] The way to introduce SnCl2 functional additives can be to add it directly to the electrolyte or to introduce it into the lithium-air battery by loading it on the diaphragm. Both methods can stabilize the DMSO electrolyte system well and improve the performance of lithium-air batteries significantly. However, the latter method can avoid the rapid attack of lithium sheets on a large scale and the SnCl2 coated on the diaphragm can be gradually released into the DMSO electrolyte to make Sn2+ The DMSO electrolyte system is always at saturated concentration to continuously stabilize the system, achieving the best effect.

[0186] SnCl2 was directly added to the electrolyte, and the concentration of SnCl2 was saturated at 0.02M;

[0187] The coating thickness of the SnCl2-loaded membrane is 100 μm-250 μm (if the coating is completely dissolved in the electrolyte, the SnCl2 concentration is 0.025 M-0.0625 M), and the performance is better than that of SnCl2 directly added to the electrolyte;

[0188] Preferably, the coating thickness of the SnCl2-loaded membrane is 150 μm-230 μm (if the coating is completely dissolved in the electrolyte, the SnCl2 concentration is 0.0375 M-0.0575 M), and the performance is significantly better than when SnCl2 is directly added to the electrolyte;

[0189] More preferably, the coating thickness of the SnCl2-loaded membrane is 180-220 μm (if the coating is completely dissolved in the electrolyte, the SnCl2 concentration is 0.045 M-0.055 M), and the performance is significantly better than when SnCl2 is directly added to the electrolyte;

[0190] Most preferably, the coating thickness of the SnCl2-loaded membrane is 200 μm (if the coating is completely dissolved in the electrolyte, the SnCl2 concentration is 0.05 M), and the performance greatly exceeds that of SnCl2 directly added to the electrolyte.

[0191] It should be pointed out that when the coating thickness of the SnCl2 loaded membrane exceeds 250 μm, the SnCl2 functional additive will be released excessively into the electrolyte system, resulting in a supersaturated solution state and solid powder precipitation, thus affecting the performance.

[0192] In the electrolyte system of the present invention using DMSO as solvent, the recommended order of lithium salts used is: LiTFSI>LiFSI>LiClO4.

[0193] The introduction of SnCl2 functional additives into the DMSO electrolyte system can form complex molecules to stabilize the electrolyte system, which is caused by the strong selectivity between specific organic solvents and specific inorganic metal halides. For the TEGDME electrolyte system, no matter which method (introduced into the electrolyte and / or introduced onto the diaphragm) the SnCl2 functional additive is introduced, the performance of the lithium-air battery is relatively limited. Similarly, the SnCl2 functional additive cannot stabilize the PC electrolyte system no matter which method (introduced into the electrolyte and / or introduced onto the diaphragm). In addition, SnBr2, SnI2, and ZnCl2 cannot stabilize the DMSO electrolyte system.

Claims

1. A lithium-air battery, characterized in that: The invention comprises a positive electrode, a negative electrode, a separator between the positive and negative electrodes, an electrolyte and a metal inorganic salt additive. The electrolyte comprises a lithium salt and an organic solvent. The organic solvent is dimethyl sulfoxide (DMSO). The inorganic salt additive is SnCl2. The SnCl2 is added by directly introducing it into the electrolyte and / or introducing it onto the separator.

2. The lithium-air battery according to claim 1, characterized in that The lithium salt is a mixture of one or more of lithium bis(trifluoromethanesulfonyl)imide LiTFSI, lithium bis(fluorosulfonyl)imide LiFSI, and lithium perchlorate LiClO4; the concentration of the lithium salt in the electrolyte is 0.1-10 mol / L, preferably 1 mol / L.

3. The lithium-air battery according to claim 1 or 2, characterized in that: SnCl2 is directly introduced into the electrolyte, and the concentration of SnCl2 in the electrolyte is a saturated concentration of 0.02M; and / or SnCl2 is introduced into the diaphragm by mixing SnCl2 with a binder and a conductive agent in an organic solvent to form a slurry, which is then coated on a carrier to form a SnCl2 loaded film. The SnCl2 loaded film and the carrier are an integral whole, called a composite diaphragm. The composite diaphragm is placed between the diaphragm and the negative electrode. The SnCl2 loaded film is in contact with the diaphragm, and the carrier is in contact with the negative electrode. The coating thickness of the SnCl2 loaded film is 100μm-250μm, preferably 150μm-230μm, more preferably 180-220μm, and most preferably 200μm.

4. The lithium-air battery according to claim 3, characterized in that: The method of introducing SnCl2 onto the diaphragm includes the following steps: SnCl2, a binder and a conductive agent are mixed in nitrogen methyl pyrrolidone (NMP) at a mass ratio of 7:2:1, with NMP being 4 times the total mass of the solute, and stirred for 5 hours to obtain a mixed slurry; the mixed slurry is then coated on a carrier and vacuum dried to obtain a composite diaphragm.

5. The lithium-air battery according to claim 3, characterized in that: The negative electrode is a lithium sheet; and / or the positive electrode is carbon paper loaded with Ketjen black; and / or the separator is a glass fiber separator.

6. The method for preparing a lithium-air battery according to any one of claims 1 to 5, characterized in that: The steps include: In a glove box, lithium salt and metal inorganic salt additive SnCl2 are added to DMSO, mixed evenly to obtain an electrolyte, and then the positive electrode, separator, negative electrode and electrolyte are assembled into a lithium-air battery; or First, the metal inorganic salt additive SnCl2 is mixed with a binder and a conductive agent in an organic solvent to form a slurry, which is then coated on a carrier to form a SnCl2 loaded film. The SnCl2 loaded film and the carrier are an integral whole, called a composite diaphragm. Subsequently, in a glove box, lithium salt is added to DMSO and mixed evenly to obtain an electrolyte. Then, the positive electrode, diaphragm, composite diaphragm, negative electrode and electrolyte are assembled into a lithium-air battery. The SnCl2 loaded film in the composite diaphragm is in contact with the diaphragm, and the carrier is in contact with the negative electrode.

Citation Information

Cited By

  • Electrolyte for lithium air battery and lithium air battery

    CN121416616A

  • An electrolyte for a lithium-air battery and a lithium-air battery

    CN121416616B